EnSenias: Technological tool to learn, teach, improve and use Panamanian Sign Language - Rodríguez-Fuentes, Antonio; Alain, Lineth; García García, Francisco (Íkala, Revista de Lenguaje y Cultura, 2020)
Communication has always been a requiremente for society advancement, and technology has recently become a vehicle for its expansion. The deaf community has found some limitations in this area, and, therefore, requires additional support. This mixed, non-experimental, descriptive study focuses on EnSenias, an online platform that can be used to learn, teach, improve, and use Panamanian sign language, and has as its main purpose to explore its functionality and validity. This study was carried out at the Panamanian Institute for Special Enabling. To carry it out, data were gathered through twelve focus groups (with 57 participants), and analyzed using mixed analysis techniques. The results of the analysis show that EnSenias is necessary and suitable to learn the sign language, provides universal accesibility, is useful to learn and teach sign vocabulary, and serves as an elementary dictionary and translator in sign language. Its affordability allows deaf, hearing-impaired, hearing, blind, short-sighted, and deaf-blind people to learn sign language.